2019
DOI: 10.3390/polym11101598
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Solution Deposition of Ordered 2D Arrays of Room-Temperature Ferrimagnetic Cobalt Ferrite Nanodots

Abstract: Over the past decades, the development of nano-scale electronic devices and high-density memory storage media has raised the demand for low-cost fabrication methods of two-dimensional (2D) arrays of magnetic nanostructures. Here, we present a chemical solution deposition methodology to produce 2D arrays of cobalt ferrite (CFO) nanodots on Si substrates. Using thin films of four different self-assembled block copolymers as templates, ordered arrays of nanodots with four different characteristic dimensions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…A final calcination step removes all organic components and transformed the iron ions of the inner shell into iron oxide, leading to inorganic hollow double-shell nanospheres [23]. A similar approach is demonstrated on vapor-annealed thin films of a PS-b-PEO diblock copolymer by Jin Xu et al [24], where the cylindrical PEO domains are loaded with iron and cobalt ions, followed by an oxidative and thermal treatment to yield regularly arranged, ferrimagnetic cobalt ferrite nanodots with suitable transition temperature to superparamagnetic nanodots, making them interesting candidates for memory storage applications. A systematic study of vapor annealing to equilibrate polystyrene-block-poly(2-vinylpyridine) diblock copolymer films and corresponding homopolymers using in situ spectroscopic ellipsometry and different microscopies is presented by Xiao Cheng et al, who found the temperatures of the substrate and the solvent vapor to be main controlling parameters influencing the dynamics of equilibration [25].…”
mentioning
confidence: 89%
“…A final calcination step removes all organic components and transformed the iron ions of the inner shell into iron oxide, leading to inorganic hollow double-shell nanospheres [23]. A similar approach is demonstrated on vapor-annealed thin films of a PS-b-PEO diblock copolymer by Jin Xu et al [24], where the cylindrical PEO domains are loaded with iron and cobalt ions, followed by an oxidative and thermal treatment to yield regularly arranged, ferrimagnetic cobalt ferrite nanodots with suitable transition temperature to superparamagnetic nanodots, making them interesting candidates for memory storage applications. A systematic study of vapor annealing to equilibrate polystyrene-block-poly(2-vinylpyridine) diblock copolymer films and corresponding homopolymers using in situ spectroscopic ellipsometry and different microscopies is presented by Xiao Cheng et al, who found the temperatures of the substrate and the solvent vapor to be main controlling parameters influencing the dynamics of equilibration [25].…”
mentioning
confidence: 89%
“…10), 136 thereby leading to self-assembly into different morphologies. [137][138][139][140][141][142] Self-assembly in BCP thin films is more complicated. Parameters like film thickness, substrate interaction with each block, and free surface selectivity can influence the morphology significantly.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…This is one of the few reports of the fabrication of complex oxides using BCP templating. 142,152 Horizontal morphologies (with no or limited long range order) such as lamella or horizontal cylinders are not often used for templating of metal oxides using CSD. Previously, metallic nanostructures have been formed using lamellar BCP and CSD to…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
See 2 more Smart Citations